Induction of erythropoietin responsiveness in murine hematopoietic cells by the gag-myb-ets-containing ME26 virus. - Ruscetti, S (1992)
ME26 virus, which was generated by inserting the coding region of the acute avian leukemia-inducing virus E26 into a murine retrovirus vector, encodes a 135-kDa gag-myb-ets fusion protein. Amphotropic murine leukemia virus pseudotypes of ME26 virus induce a high incidence of erythroleukemia 2 to 4 months after injection into newborn NFS/N mice. Spleen cells from the majority of these mice proliferate to high levels in the presence of the erythroid hormone erythropoietin (Epo) and can easily be established as permanent Epo-dependent cell lines. The cell lines contain multiple copies of ME26 viral DNA and express viral message and protein. An Epo receptor mRNA of normal size can be detected in these cells, and binding studies reveal a single class of lower-affinity Epo receptor with an affinity for Epo that is in the range of that previously reported for erythroid cells. The ME26 virus-induced Epo-dependent cell lines, however, appear more immature than previously described erythroid cell lines and more closely resemble early hematopoietic precursor cells, suggesting that the virus may be activating the Epo receptor in hematopoietic cells that do not normally express it. Consistent with this idea, we are able to infect an interleukin-3-dependent myeloid cell line, FDC-P2, with ME26 virus and convert it to Epo dependence. The ME26 virus-infected FDC-P2 cells, even before growth on Epo, showed a large increase in the amount of Epo receptor mRNA. However, no ME26 viral integrations can be detected adjacent to the Epo receptor gene, indicating that the virus is not activating the Epo receptor gene by promoter/enhancer insertion. Our results are more consistent with the hypothesis that the gag-myb-ets-encoded viral fusion protein, which is known to bind DNA, is directly or indirectly activating the expression of the Epo receptor gene in these cells.